Human Resources Management in Improving Company Performance - Abdul Haris Muchtar; Ahmad Maulidizen; Sujoko Winanto (International Journal of Education, Information Technology, and Others, 2022)
Human resource planning is a very important activity to meet the needs of organizational staff as a result of organizational changes in the face of a dynamic and complex business environment. This paper aims to explain the management of human resources in improving company performance. This paper is a literature review that analyzes reference sources from journals, books and websites that discuss project management conceptually and comprehensively. This paper uses the method of collecting data in documentation, as well as various articles and books. Then analyzed using content analysis, namely by analyzing descriptive literature data or scientific analysis of the message of a premise. While the data analysis method is deductive, inductive and comparative. The findings of the paper are that human resource planning is the process of planning manpower to suit the company's needs effectively and efficiently in helping the realization of company goals. Of all the resources available in the company, human resources are very important and decisive resources. All the potentials possessed by human resources greatly affect the company's efforts to achieve its goals. The similarity of this paper with others is to discuss human resource management conceptually, but the difference is that it is accompanied by the application of human resource management in improving company performance